An embedded real-time co-processor for control applications - Cayssials, Ricardo (2005)
In this paper we present a high performance real-time microcontroller (uRT51) based on an 8051 core. The uRT51 is an 8-bits processor that includes a Real-Time co-processing unit. We have implemented the speed control of a DC motor to evaluate the uRT51 performance. The uRT51 shows a control performance suitable for low-cost, low-power, embedded real-time control applications in which real-time systems based on RTOS fail